2016
DOI: 10.1111/etho.12123
|View full text |Cite
|
Sign up to set email alerts
|

Competing Etiologies of Trauma and the Mediation of Political Suffering: The Disengagement from the Gaza Strip and West Bank in Secular and Religious Therapeutic Narratives

Abstract: The forced evacuation of Jewish Israeli settlers from the Gaza Strip and parts of the West Bank in August 2005 (known as the Disengagement) was an extremely controversial political event in Israeli public discourse. This article seeks to explore how political differences in the public sphere were reflected in the professional narratives of mental health practitioners. Based on my field notes documenting the processes of the narration of the Disengagement within various professional settings of Israeli mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These moods and dilemmas reflect cultural patterns, yet they are situational and fragmentary. Such situated moral work often leaves the clinicians having to tolerate profound ambivalence about the goodness of their clinical tactics (Brodwin, 2013; Smith et al, 2019). The “good” for the described epistemic community has been continually redefined in accordance with various criteria: the communal goals, the definition of patient’ needs, the psychological theories on parenting and trauma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These moods and dilemmas reflect cultural patterns, yet they are situational and fragmentary. Such situated moral work often leaves the clinicians having to tolerate profound ambivalence about the goodness of their clinical tactics (Brodwin, 2013; Smith et al, 2019). The “good” for the described epistemic community has been continually redefined in accordance with various criteria: the communal goals, the definition of patient’ needs, the psychological theories on parenting and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…When approaching this study, I assumed that the therapists who identified with religious Zionism would stress the role of the traumatic event as the determining factor in the patient's suffering. This assumption was grounded on a moral grammar of traumatic narrative which implies the moral innocence of victims (Brunner, 2002;Young, 1995) and the perception of the political and moral subjectivity of the ideologically oriented psychotherapists (McKenny, 2007;Plotkin Amrami, 2016). Thus, I anticipated that the patient's symptoms would be explained in the described clinical setting as a direct result of the Disengagement experience rather than a feature of her personal qualities or her parents' functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations